THE EFFECTIVENESS OF THE "SI GEMPI AR 3D" EDUCATIONAL COMIC PROGRAM ON THE LEVEL OF UNDERSTANDING AMONG SMA NEGERI 1 KUTA MAKMUR STUDENTS REGARDING ACEH QANUN NUMBER 6 OF 2014 CONCERNING JINAYAT LAW - Desy Fatmasari; Cut Sukmawati; Lisa Iryani; Ferizaldi; Murniati (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study analyzes the effectiveness of the Si Gempi AR 3D Educational Comic in improving students' understanding of Aceh Qanun Number 6 of 2014 concerning Jinayat Law at SMA Negeri 1 Kuta Makmur. The program aims to increase legal awareness and help reduce juvenile delinquency. The research is based on Campbell J.P.'s (1990) Program Effectiveness Theory, which includes target success, program success, user satisfaction, input and output levels, and goal achievement. Students' understanding is measured using Kenneth D. Moore's (2007) Conceptual Understanding Theory. This study employs a quantitative survey method with descriptive and causal-comparative approaches. Data were collected through questionnaires distributed to 100 students selected from a population of 355 using probability sampling with a simple random sampling technique. The data were analyzed using descriptive statistics, instrument testing, classical assumption tests, and simple linear regression with SPSS. The findings show that the Si Gempi AR 3D Educational Comic has a positive and significant effect on students' understanding of Jinayat Law. The significance value is <0.001, the calculated t-value (38.358) exceeds the t-table value (1.984), and the coefficient of determination (R²) is 0.937. These results indicate that the comic effectively improves students' understanding and supports its implementation as an educational medium.